Differences in the Effectiveness of Video and Booklet Education on Early Detection, Prevention, and Management of Preeclampsia in Pregnant Women among Health Workers - Yenny Puspitasari; Suci Anggraeni; Nur Yeny Hidajaturrokhmah (Journal Of Nursing Practice, 2026)
Background: Preeclampsia is one of the leading causes of preventable maternal and fetal deaths in Indonesia if detected early. Lack of understanding about the symptoms, risk factors, and early treatment of preeclampsia remains a challenge at the community level, especially in areas with limited access to information and health services. Purpose: The purpose of this study was to analyze the differences in the effectiveness of video and booklet education on cadres' understanding of early detection, prevention, and management of preeclampsia in pregnant women. Methods: The research design was quasi-experimental, in which the researcher divided the respondents into two groups, namely video intervention and booklet intervention. The research sample consisted of 58 health cadres in Manisrenggo Village, using total sampling technique. The measurement tool used was a questionnaire on understanding early detection, prevention, and management of preeclampsia in pregnant women, which had been tested for validity and reliability. The research media used were videos and booklets. The research analysis was univariate, paired t-test, and independent t-test using SPSS 23. Results: The results showed that the mean score for cadres' understanding before the booklet intervention was 40.17, which increased to 43.41 after the booklet intervention. The p-value was 0.000, indicating that the booklet intervention had an effect on cadres' understanding of early detection, prevention, and management of preeclampsia in pregnant women among health cadres before and after the intervention. Conclusion: There is a difference in the effectiveness of video and booklet education on early detection, prevention, and management of preeclampsia in pregnant women among health cadres. Based on the mean value, video intervention is more effective than booklet intervention.